2020
DOI: 10.1172/jci.insight.132342
|View full text |Cite
|
Sign up to set email alerts
|

Chronic liver disease and impaired hepatic glycogen metabolism in argininosuccinate lyase deficiency

Abstract: BACKGROUND. Liver disease in urea cycle disorders (UCDs) ranges from hepatomegaly and chronic hepatocellular injury to cirrhosis and end-stage liver disease. However, the prevalence and underlying mechanisms are unclear. METHODS. We estimated the prevalence of chronic hepatocellular injury in UCDs using data from a multicenter, longitudinal, natural history study. We also used ultrasound with shear wave elastography and FibroTest to evaluate liver stiffness and markers of fibrosis in individuals with argininos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 54 publications
(82 reference statements)
6
19
0
Order By: Relevance
“…To this end, Asl Neo/Neo mice received protein-restricted diet and daily administration of Na-benzoate and L-Arg in combination with either TB-1 or vehicle, started on day ten of life and lasting for 3 weeks. Consistent with previous data (Ashley et al, 2018;Baruteau et al, 2018;Burrage et al, 2020;Erez et al, 2011), vehicle-treated Asl Neo/Neo mice showed vacuolated hepatocyte cytoplasm by hematoxylin and eosin (H&E) staining in contrast to WT mice, whereas TB-1 treatment markedly improved the microscopic changes of liver architecture (Fig. 3A).…”
Section: Tat-beclin-1 Reduced Injury and Abnormal Glycogen Depositionsupporting
confidence: 91%
See 4 more Smart Citations
“…To this end, Asl Neo/Neo mice received protein-restricted diet and daily administration of Na-benzoate and L-Arg in combination with either TB-1 or vehicle, started on day ten of life and lasting for 3 weeks. Consistent with previous data (Ashley et al, 2018;Baruteau et al, 2018;Burrage et al, 2020;Erez et al, 2011), vehicle-treated Asl Neo/Neo mice showed vacuolated hepatocyte cytoplasm by hematoxylin and eosin (H&E) staining in contrast to WT mice, whereas TB-1 treatment markedly improved the microscopic changes of liver architecture (Fig. 3A).…”
Section: Tat-beclin-1 Reduced Injury and Abnormal Glycogen Depositionsupporting
confidence: 91%
“…3E). Moreover, glycogen accumulation in Asl Neo/Neo mice resulted in displacement of organelles to the cell membrane as previously reported (Burrage et al, 2020), that is relieved by TB-1 ( Fig. 3E).…”
Section: Tat-beclin-1 Reduced Injury and Abnormal Glycogen Depositionsupporting
confidence: 87%
See 3 more Smart Citations